The Influence of Self-Efficacy, Leadership Style, and Emotional Intelligence on Employee Performance - Nur Halimah; Kartika Sari Lubis (Husnayain Business Review, 2025)
This study aims to analyze the influence of self-efficacy, leadership style, and emotional intelligence on employee performance at PT Pelabuhan Indonesia Regional 1. The research employed a quantitative approach with 100 respondents as samples, and data were collected through questionnaires. The data were analyzed using SPSS version 26 with multiple linear regression techniques. The results indicate that self-efficacy, leadership style, and emotional intelligence each have a positive and significant effect on employee performance, both partially and simultaneously. These findings demonstrate that confidence in one’s abilities, effective leadership, and strong emotional management play crucial roles in enhancing employee performance. The study recommends that companies continuously develop leadership quality and emotional competence programs to improve overall organizational productivity.